New Phenolic Glycosides and Lignans from the Roots of Lilium dauricum - Xia, Xiao; Zhang, Jiao; Wang, Xiao-Jiang; Lu, Yan; Chen, Dao-Feng (Planta Medica, 2021)
Three new phenolic glycosides, carvacrol-2-O-β-D-apiofuranosyl-(1 → 6)-β-D-glucopyranoside (1), 1-methyl-3-isopropylphenol-4-O-β-D-apiofuranosyl-(1 → 6)-β-D-glucopyranoside (2), p-methoxythymol-5-O-β-D-apiofuranosyl-(1 → 6)-β-D-glucopyranoside (3), and a pair of new 8-O-4′ neolignan enantiomers (5a/5b), together with 26 known compounds (4, 6 – 30) were isolated from the roots of Lilium dauricum. The structures of the new compounds were elucidated based on extensive spectroscopic and chemical methods, and the absolute configurations of 5a and 5b were established by electronic circular dichroism analysis. Nine compounds (1, 3, 4, 8, 9, 17, 25, 29, and 30) exhibited potent α-glucosidase inhibitory activity with IC50 values ranging from 73.4 µM to 988.2 µM. Besides, compound 19 displayed strong anticomplementary activity (CH50: 71.6 µM).
Keywords: Liliaceae; Lilium dauricum; phenolic glycosides; lignans; α-glucosidase inhibitory activity